2018
DOI: 10.5433/1679-0359.2018v39n6p2443
|View full text |Cite
|
Sign up to set email alerts
|

Associação do histórico de abortamento com a presença de anticorpos anti-Neospora caninum em vacas leiteiras

Abstract: Neospora caninum is an important cause of abortions in dairy cattle, leading to severe economic losses. The objective of this study was to determine the association of serum antibodies against N. caninum with a history of abortion in dairy cows. A total of 46 dairy cows from nine dairy farms were evaluated; 28 with a history of one or more abortions and 18 without a history of abortions. Antibodies against N. caninum were detected by indirect immunofluorescence, and the reaction was considered positive when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Mazuz et al (2014) in a study of pregnant cows, found that the percentage of abortions in N. caninum seropositive cows was three times higher than in seronegative cows. Frigotto, Genz, Nino, Zulpo and Garcia (2018), studying N. caninum in dairy cows, observed an association between seropositive cows and history of abortion; the authors reported that cows with a history of abortion were 10.6 times more likely to be seroreactive than cows without a history of abortion. Our work further reinforces the relationship between abortion and N. caninum seropositivity, but we must not forget that T. gondii was also identified as a risk factor associated with abortion, so this etiological agent should also be included as a differential in reproductive cases of this species.…”
Section: Resultsmentioning
confidence: 99%
“…Mazuz et al (2014) in a study of pregnant cows, found that the percentage of abortions in N. caninum seropositive cows was three times higher than in seronegative cows. Frigotto, Genz, Nino, Zulpo and Garcia (2018), studying N. caninum in dairy cows, observed an association between seropositive cows and history of abortion; the authors reported that cows with a history of abortion were 10.6 times more likely to be seroreactive than cows without a history of abortion. Our work further reinforces the relationship between abortion and N. caninum seropositivity, but we must not forget that T. gondii was also identified as a risk factor associated with abortion, so this etiological agent should also be included as a differential in reproductive cases of this species.…”
Section: Resultsmentioning
confidence: 99%